Output Feedback Control For Trajectory Tracking Of Wheeled Mobile Robot. Issue 1 (2nd January 2016) - Asif, Muhammad; Memon, Attaullah Y.; Junaid Khan, Muhammad
Abstract: In this paper, output feedback control for trajectory tracking of a wheeled mobile robot (WMR) is proposed using a high gain observer. Kinematic and dynamic models of the WMR are described, and an output feedback controller is proposed using adaptive sliding mode controller. High gain observer is designed for velocity estimation of WMR trajectory tracking. It is shown that using high gain observer and a globally bounded state feedback stabilizing controller, the close-loop system performance can be recovered in the presence of un-modeled dynamics and disturbances. Stability analysis of the proposed observer is shown using Lyapunov methods. The effectiveness of the proposed system is shown using simulation.